Penatalaksanaan Fisioterapi Sensorimotor pada Anak dengan Autism Spectrum Disorder: Studi Kasus di PNTC Colomadu - Ryan Putra Samodra; Amalia Solichati rizki; Yudha Wahyu Putra (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2026)
Autism Spectrum Disorder (ASD) is a neurobiological developmental disorder that impacts communication skills, social interactions, behavioral patterns, and processing of children's behavioral processes. The increasing incidence of ASD in children demonstrates the importance of implementing appropriate interventions, including physiotherapy, to optimize sensory, motor, and functional development in children. This study aims to evaluate examination results and determine the effect of physiotherapy interventions on sensory abilities, balance, and functional activities in children with ASD. This study used a descriptive case study design on a child with ASD who underwent six therapy sessions at PNTC Colomadu from January 9 to 26, 2026. The evaluation was conducted using the Short Sensory Profile (SSP), Pediatric Balance Scale (PBS), and Pediatric Evaluation of Disability Inventory (PEDI) instruments. The intervention program provided included Neuro Sensory Motor Reflex Development and Synchronization (NSMRD&S), brain gym, oral massage, and massage with a therapy duration of approximately 60–90 minutes per session. The results of the study indicate that children's balance abilities are in the good category and tend to be stable based on the PBS measurement results. In the sensory aspect, obstacles were still found in processing environmental stimuli, but the children's responses to stimuli showed a more focused and adaptive improvement. Furthermore, functional activity abilities showed a fairly good level of independence in several daily activities, although assistance or supervision was still required for certain activities. Overall, physiotherapy interventions contributed positively to maintaining and supporting the development of sensory abilities, balance, and functional activities in children with ASD, although clinical changes obtained during the intervention period did not show significant improvement.